2020
DOI: 10.21203/rs.2.24511/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychosocial Family Interventions for Relatives of People Living with Psychotic Disorders in the Arab World: Systematic Review

Abstract: Aim and objectives: To synthesise the available evidence about culturally-adapted psychosocial family interventions in the Arab world. The review identifies the content and characteristics of these interventions, determines the strategies used to adapt them to the Arab culture successfully, assesses the feasibility and acceptability of the interventions, and evaluates the effectiveness of these interventions for service users and their families. Background: Family interventions in schizophrenia are evidence-ba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The associated preventive capacity is, however, limited: while a meta‐analysis found that selective psychoeducational interventions may have a small effect on reducing the severity and incidence of depression in the offspring of patients 136 , the preventive efficacy of other psychosocial interventions in young individuals with a familial vulnerability for psychotic 137 , bipolar 138 or anxiety disorders is currently unknown.…”
Section: Evidence Supporting Primary Prevention and Mental Health Promotion In Young Peoplementioning
confidence: 99%
“…The associated preventive capacity is, however, limited: while a meta‐analysis found that selective psychoeducational interventions may have a small effect on reducing the severity and incidence of depression in the offspring of patients 136 , the preventive efficacy of other psychosocial interventions in young individuals with a familial vulnerability for psychotic 137 , bipolar 138 or anxiety disorders is currently unknown.…”
Section: Evidence Supporting Primary Prevention and Mental Health Promotion In Young Peoplementioning
confidence: 99%
“…The Medical Research Council (MRC) framework for the development and evaluation of complex interventions was used to guide the structure of this study. (19), ( 21)…”
Section: Study Design and Purposementioning
confidence: 99%